Comparison Between Gow-Gates Mandibular Nerve Block Versus Inferior Alveolar Nerve Block in Extraction of Mandibular Third Molars: Gow-Gates Mandibular Nerve Block Versus Inferior Alveolar Nerve Block - Rehman, Saif ur; Channar, Kashif Ali; Memon, Waqas; Kumbhar, Aftab Ahmed; Bilgrami, Afreen; Javed, Farhan (Pakistan Journal of Health Sciences, 2024)
Because of the intricacy of the process and the possibility of severe patient suffering, a successful extraction of mandibular third molars, or wisdom teeth, depends on an effective anesthetic. Objective: To compare the efficacy of Gow-Gates Mandibular Nerve Block (GGNB) versus Inferior Alveolar Nerve Block (IANB) in the extraction of mandibular third molars. Methods: This comparative cross-sectional study involved patients aged 20 to 45 years, of both genders, with impacted mandibular third molars. Using non-probability consecutive sampling, 160 patients were allocated to two groups: Group A (IANB) and Group B (GGNB), each with 80 patients. Outcomes such as pain, onset of anesthesia, and post-operation recovery time were measured. Efficacy between the groups was compared using Chi-square and independent t-tests. Results: The mean age was 30.29 ± 6.96 years. The mean pain in IANB (1.43 ± 1.19) was lower than in Gow-Gate (1.59 ± 2.02) statistically (p = 0.041). For anesthetizing the buccal, inferior alveolar nerve, and lingual nerve shows that only the buccal nerve the GGNB (100%) was more effective than IANB (81.5%) statistically (p<0.001). The onset of anesthesia was quicker in GGNB than in IANB for all three nerves (p<0.001). Post-operative recovery time between IANB and GGNB techniques was not statistically different (p=0.227). Conclusions: The research concluded that IANB resulted in significantly lower pain compared to GGNB. GGNB demonstrated greater effectiveness in anesthetizing the buccal nerve compared to IANB. The onset of anesthesia was statistically quicker in GGNB than in IANB for all three nerves.